Filosofia y literatura clave de la cultura Hispanica . - Gonzalez, Angela Sierra, Torres, Juan Manuel Diaz, Fuentes, Jesus Luis Paradinas; et. al (Biblioteca de Humanidades (Fundacion fernando Rielo), 3., 2006)
Papers from a conference hosted by the Fundacion Fernando Rielo and the Universidad de La laguna, March 15-19, 2004.